Presidential Address - Quarter century of systemic fungicides status and challenges ahead - CHATRATH, M. S. (Indian Phytopathology, 2002)
I am thankful to the members of the Indian Phytopathological Society for the honour they have done me by electing me as President of the society for the year 1992. I express my gratefulness in all sincerity and in no way because it is customary to do so on such formal occasions. The subject which I have chosen for today's address in comparatively of recent development and our knowledge in this field has advanced at a remarkably fast pace. I will like not only to project the present status of the available information on some of the aspects of systemic fungicides but also to share thought on some of the problems and the trends which are emerging in this field alongwith the future needs for research with this galaxy of plant pathologists of our country.